Implementation of Javanese Speech as a Form of Strengthening Local Wisdom for Middle School Teachers in Ngargoyoso District, Karanganyar Regency - Basuki Sumartono; Sutarjo Sutarjo; Deniawan Tommy Chandra Wijaya (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Javanese speech is a way of someone with special skills in Javanese literature and language who is able to bring events in Javanese society, such as weddings (temanten), death (kesripahan), meetings (pepanggihan), banquets (pasamuan), recitation (pengaosan), stage, and so on. Partner problems experienced, namely (1) there are still Javanese language teachers who have not mastered Javanese speech techniques according to the correct rules; (2) Junior high school Javanese language teachers in Ngargoyoso District have not all mastered Javanese language and literature in Javanese speeches; (3) Not all middle school Javanese language teachers in Ngargoyoso District know and understand paramasastra (phonology, morphology, semantics, syntax), discourse, and Javanese pragmatics; (4) Not all middle school Javanese language teachers in Ngargoyoso Subdistrict master Hamicara (Public Speaking); (5) Not all middle school Javanese language teachers in Ngargoyoso Subdistrict have confidence in giving Javanese speeches. The implementation method used is by using the practice/practice method, listening and elearning where the activity planning is expected to answer Javanese speech skills for junior high school teachers in Ngargoyoso District, Karanganyar Regency, Central Java. Plans for implementing program activities include (1) making video tutorials on examples of Javanese speeches as e-learning materials; (2) Conducting courses/training in Javanese speech by presenting experts; (3) Provide assistance in training in Javanese speech until proficient; and (4) To evaluate gradually. The planned outputs are (1) Publication of service in journals with ISSN or proceedings of seminars with ISBN; (2) Publication of service activities in print or online mass media; and (3) Publication of service in the form of activity videos.Keywords: Javanese speech, local wisdom, middle school, Ngargoyoso, Karanganyar.